Bridging the Gap: Help Seeking Behavior and Mental Health Service Utilization Among Indonesian Adolescents - Kartiani, Andi (Medicor : Journal of Health Informatics and Health Policy, 2024)
Adolescent mental health has become a critical public health priority in low- and middle-income countries (LMICs), yet the use of professional services remains very limited. This study investigates patterns of help-seeking behavior and mental health service utilization among Indonesian adolescents, drawing on nationally representative data from the 2022 Indonesia National Adolescent Mental Health Survey (I-NAMHS). The main objective is to identify how adolescents access formal and informal support systems, and to analyze key barriers that prevent engagement with professional care. A cross-sectional design was applied to 7,866 adolescents aged 10–17 years across 34 provinces. Mental health status was assessed using DSM-5 criteria via the MINI-KID diagnostic tool, while help-seeking behavior was measured with structured questionnaires completed by adolescents and their caregivers. Data were analyzed using descriptive statistics and logistic regression to determine service utilization patterns and predictors. Results show that only 2.6% of adolescents with a diagnosed disorder accessed formal mental health services in the past year. In contrast, 43.8% sought help from family or friends and 38.2% accessed school-based counseling. Stigma (40%), limited service availability (25%), high costs (20%), and low awareness (15%) were identified as the main barriers. Service use was higher among urban adolescents, females, and those with better-informed caregivers, highlighting significant sociodemographic disparities. This study emphasizes the urgent need to expand adolescent mental health services in Indonesia. Practical implications include strengthening school-based interventions, implementing nationwide anti-stigma campaigns, and improving caregiver mental health literacy. Building culturally responsive and integrated systems of care is essential to close the treatment gap and ensure equitable access for all Indonesian adolescents.